2018
DOI: 10.3847/1538-3881/aaa6c4
|View full text |Cite
|
Sign up to set email alerts
|

YSOVAR: Mid-infrared Variability among YSOs in the Star Formation Region Serpens South

Abstract: We present a time-variability study of young stellar objects (YSOs) in the Serpens South cluster performed at 3.6 and 4.5 μm with the Spitzer Space Telescope; this study is part of the Young Stellar Object VARiability project. We have collected light curves for more than 1500 sources, including 85 cluster members, over 38 days. This includes 44 class I sources, 19 sources with flat spectral energy distributions (SEDs), 17 class II sources, and five diskless YSO candidates. We find a high variability fraction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 57 publications
5
28
0
Order By: Relevance
“…This results in large amplitude fluctuations of its total luminosity, a swelling of the stellar radius and a decrease of the flux released in the protostar's associated H II region. Under our assumptions, we calculate within the 10−th and 90−th percentile of the collection of bursts in our simulations of forming massive stars, the extend of their luminosity variations is ≈ 0.69, which is much larger than that observed for low-mass protostars (Wolk et al 2018). This constitutes a major difference between the high-and low-mass regimes of star formation, to be verified by means of future observations.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…This results in large amplitude fluctuations of its total luminosity, a swelling of the stellar radius and a decrease of the flux released in the protostar's associated H II region. Under our assumptions, we calculate within the 10−th and 90−th percentile of the collection of bursts in our simulations of forming massive stars, the extend of their luminosity variations is ≈ 0.69, which is much larger than that observed for low-mass protostars (Wolk et al 2018). This constitutes a major difference between the high-and low-mass regimes of star formation, to be verified by means of future observations.…”
Section: Resultsmentioning
confidence: 74%
“…11b) gives ∆ [10,90] 1−mag = 0.69 mag. Particularly, one can compare the obtained burst variations with the value of 0.22 found for low-mass sources at 3.6 µm in the context of low-mass stellar objects in the Serpens South star formation region (Wolk et al 2018). According to our study, the average luminosity variation in massive star formation is larger than that in low-mass star formation, which constitutes a remarkable difference between these two regimes.…”
Section: The Scatter In Burst Magnitudes Is Wider In Massive Star Formentioning
confidence: 84%
“…There are three major differences between our class color and class SED YSO classification schemes. We include a separate flat spectrum class in order to match our SED based classification scheme with the Wolk et al (2018) YSOVar paper on Serpens South and our previous Serpens Main work (Winston et al 2007). We combine the class 0 and class 1s into class I due to the lack of far-IR or submm photometry to securely differentiate between them.…”
Section: X-ray Luminous Ysosmentioning
confidence: 99%
“…Exploring PMS variability in different regions of the electromagnetic spectrum provides insights into the physical processes at work in these systems. Optical and infrared (IR) variability studies as the Young Stellar Object (YSO) Variability Spitzer Space Telescope program (YSOVAR Morales-Calderón et al 2011;Rebull et al 2014;Wolk et al 2018) and the Coordinated Synoptic Investigation of NGC 2264 (e.g., Cody et al 2014;Guarcello et al 2017Guarcello et al , 2019 have shown that most of the variability of a YSO is related to physical phenomena happening in the disk or due to the star-disk interaction. In disk-bearing PMS stars, the stardisk interaction and the accretion process causes variability due to the rotational modulation of hot spots at the stellar surface, which are produced at the base of the accretion column (e.g., Full Tables 1−5 and the light-curves of the stars analyzed in this study are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.…”
Section: Introductionmentioning
confidence: 99%